Performance Evaluation of an Optimized Floating Breakwater in Oblique Waves with a Higher-Order Boundary Element Method - Mahmuddin, Faisal; Kashiwagi, Masashi (Makara Journal of Technology, 2014)
In the previous study, the optimal performance of a two-dimensional (2D) floating breakwater shape was obtained. The performance of this shape was also confirmed with a model experiment in a towing tank. Moreover, the shape’s performance in three dimensions (3D) was investigated in a subsequent study. However, to predict the shape’s performance in a real application more accurately, the shape’s characteristics in oblique waves must also be evaluated. In this study, the performance and characteristics of the model (hydrodynamic forces, body motions, wave elevations, and drift forces) are computed using a higher-order boundary element method (HOBEM). The HOBEM, which is based on the potential flow theory and uses quadratic representation for quadrilateral panels and velocity potentials, can be used to obtain more accurate results with fewer panels compared to the conventional panel method (CPM). The computational accuracy is confirmed by using Haskind-Newman and energy conservation relations. In this study, 3D wave effects were verified, and the body motions were much smaller compared to the 2D case. In addition, although the performance in terms of wave elevations depends on the measurement positions, the optimal performance obtained in the 2D case can be realized for a longer body length.